Development of A Literacy-Appropriate Health Education Package to Create Awareness of Periodontal Disease and Diabetes - Mohd-Said, Shahida; Mohanad Zaimi, Nur Liyana; Ruslan, Muhammad Razwan; Bin Mohd Zain, Muhammad Azuan; Mohd-Dom, Tuti Ningseh (Journal of Dentistry Indonesia, 2015)
Low oral health literacy has been associated with poor awareness and understanding of oral health care needs among diabetes patients. Specifically, the association between diabetes and periodontal disease is not known to them. Objective: To develop a literacy-appropriate health education package to create public awareness on periodontal disease and diabetes. In spite of the rising prevalence of both diseases, many people remain unaware of their early signs and relationship with each other. Methods: We divided the study into three phases: needs assessment, development of the package and evaluation of the package. Phase 1 was conducted via a Focus Group Discussion (FGD) involving periodontitis patients with diabetes recruited from the UKM Dental Faculty patient list. For phase 2, we developed three video clips of 5-minutes duration each, based on the themes that emerged from the FGD. Phase 3 was conducted using a set of self-administered questionnaires distributed to the public and patients. Results: Sixty respondents viewed the videos and at least 95% found them interesting, easily understood, useful and satisfactory. There were however some suggestions for improvement. Conclusion: The health education package developed in this study was literacy-appropriate for the general public and should be made accessible to them.